2-D wavelength/time MDW code optimization for cardinality enhancement in OCDMA system
The explosive growth of bandwidth demand, together with advance in latest communication services and emerging applications has inspired huge interest in application of code division multiple access (CDMA) technique in optical network. As a core of an optical code division multiple access (OCDMA) system, several multiple access techniques have been created for optical fiber correspondence. The aim of using OCDMA is to overcome the multiple access interference (MAI) noise and phase induced intensity noise (PIIN) which encourages the amount of bit error rate (BER). The MAI and PIIN can be reduced and suppress by using the perfect code property with minimum crosscorrelation. In this thesis, the incoherent two-dimensional (2-D) wavelength/time (W/T) modified double weight (MDW) code OCDMA is analysed and demonstrated. The allocation of W/T in this thesis is to make the system asynchronously continuous with time without any objection. The good result in optimum PIIN suppression in comparison within the proposed 2-D MDW code with other codes such as 2-D Perfect Difference Code (PDC) and 1-D MDW code. The 2-D W/T MDW code achieves high scalability with the improvement in term of cardinality, bit rate, bit error rate (BER) and distance. At 10-9 (BER), the code cardinality reaches 251 simultaneous number of users and the lowest effective received power ( ) is achieved at -16.5 dBm. By comparing within parameter; avalanche photodiode (APD) are achieved 19 km longer compare with PIIN photodiode there is 18 km in this system. Thus, the 2-D W/T MDW OCDMA code simulation has successfully reduced MAI and suppress PIIN which result in optical fiber length and effective received power.